Efficiency ACP Building Materials of BIM 5D Glodon - Windarti, Fina; Poerwoningsih, Dina; Budiyanto, Hery (Proceedings of International Conference of Graduate School on Sustainability, 2025)
BIM (Building Information Modeling) is a method that enhances efficiency in terms of time, cost, volume, and form visualization. The fundamental value of BIM is that it can dramatically improve the processes, expertise, and fragmentation within construction industry organizations by increasing the level of collaborative integration, thereby enhancing industry productivity. The efficiency of materials used in the construction industry is a crucial factor affecting the final project's cost, time, and quality. Aluminum Composite Panel (ACP) is often used as a facade material in modern buildings because of its aesthetic, durability, and ease of installation advantages. However, ACP materials undergo a relatively long ordering process because most of these materials are not produced in Indonesia, which requires additional time for import. Inefficient management of ACP materials (cutting size) can cause waste and increase costs. This study aims to analyze the efficiency of ACP material use in construction projects using Glodon software, an application based on Building Information Modeling (BIM), specifically 5D BIM, which can accurately calculate material quantities. This study aims to provide insights into the efficiency of Glodon software for architects in Indonesia, offering a quick alternative design method that prioritizes waste efficiency to reduce waste emissions, in line with the concept of green building. Efficiency in material waste management contributes to the development of green buildings because reduced waste means a more efficient use of resources and a lower environmental impact. Many green building standards and systems, such as LEED (Leadership in Energy and Environmental Design), assess material efficiency as one of the criteria in the overall assessment of green buildings. This study employed a quantitative descriptive method through a case study of a construction project utilizing ACP. This study also analyzes the potential for reducing material waste by utilizing Glodon software for the first and second calculation stages, employing Maxcut software, and its impact on project costs and time. The application of Glodon also contributes to accelerating the time to manage ACP cutting patterns and waste calculations. If you want even smaller waste, Maxcut software determines efficient cutting patterns to reduce project costs because the waste is relatively small. Factors that affect the efficiency of ACP materials identified include the level of calculation accuracy, material management in the field, and user skills in operating Glodon software, significantly increasing the efficiency of ACP material use and suggesting wider use of 5D BIM technology in material management in the construction industry to achieve more efficient and environmentally friendly projects.